One important lesson I’ve learned from my involvement with SoTL - Mighty, Joy (Teaching and Learning Inquiry, 2013)
As a regular feature in Teaching & Learning Inquiry, we will ask leading thinkers in the field of SoTL to articulate one important lesson they have learned over the course of their careers. In this first installment, Joy Mighty talks about leadership in its numerous forms, from individual to institutional, and its potential for the development of SoTL. Before becoming the Associate Vice-President, Teaching and Learning, at Carleton University in Ottawa, Joy was the Director of the Centre for Teaching and Learning and Professor in the School of Business at Queen’s University in Canada. Joy has also served as the President of the Society for Teaching and Learning in Higher Education, and is the co-editor of Taking Stock: Research on Teaching and Learning in Higher Education.